Continuous and Distributed Systems Theory and Applications - Zgurovsky, Mikhail Z.; Sadovnichiy, Victor A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
In this volume, the authors close the gap between abstract mathematical approaches, such as abstract algebra, number theory, nonlinear functional analysis, partial differential equations, methods of nonlinear and multi-valued analysis, on the one hand, and practical applications in nonlinear mechanics, decision making theory and control theory on the other. Readers will also benefit from the presentation of modern mathematical modeling methods for the numerical solution of complicated engineering problems in hydromechanics, geophysics and mechanics of continua. This compilation will be of interest to mathematicians and engineers working at the interface of these field. It presents selected works of the open seminar series of Lomonosov Moscow State University and the National Technical University of Ukraine (3z(BKyiv Polytechnic Institute(3y(B. The authors come from Germany, Italy, Spain, Russia, Ukraine, and the USA.s
From the Contents: Part I Abstract Algebra and Applications -- Part II Mechanics and Numerical Methods -- Part III Long-time Forecasting in Multidisciplinary Investigations -- Part IV Control Theory and Decision Making -- Part V Short Communications.
Keywords: Engineering; Chemistry, Physical organic; Systems theory; Mechanics, applied; Engineering; Theoretical and Applied Mechanics; Systems Theory, Control; Physical Chemistry